The Important Of Technology Implementation in Learning English - Community Empowerment of Thai Society - Syahputri, Veni Nella; Eldo, Handry; Nyak Mutia Ismail (Bansigom Na Publisher, 2024)
This study explores the significance of technology implementation in English language learning and its impact on community empowerment in Thailand. With the rapid advancement of technology, the use of digital tools in English education has become crucial in enhancing accessibility and effectiveness. This research employs a qualitative approach to assess how technologies such as learning apps, online platforms, and multimedia tools have influenced English learning processes within Thai communities. Through in-depth interviews with educators, students, and community members, as well as documentation analysis of technology use in education, the study identifies key benefits, challenges faced, and successful implementation strategies. Findings indicate that technology not only improves individual English language skills but also empowers communities by increasing educational opportunities and job skills. The study recommends further development of technology-based programs and policy support to expand the benefits of technology in English learning within Thai communities.